Health education: Using eye masks, ear plugs, and white noise to improve sleep quality for critical patients in the ICU at Bandung City Hospital - Nurhayati, Nunung; Waluyo, Agung; Kariasa, I Made; Asih, Sali Rahadi; Pujasari, Hening; Hayat, Bahrul (Universitas Negeri Yogyakarta, 2024)
Sleep quality is an important factor in a person's physical and mental health. Noise, pain, light, and nursing activities are frequent causes of poor sleep quality in ICU patients. Nurses' knowledge is considered important in improving the quality of patient sleep, so health education is needed for ICU nurses in carrying out interventions to optimize the sleep quality of critical patients in the ICU. Eye masks, ear plugs and white noise are interventions to deal with noise and light in critical patients. This therapy aims to improve the quality of the patient's sleep. This health education is carried out to optimize the implementation of nursing care for patients in the ICU. Method: This community service method is carried out using a direct health education approach located in several hospitals in Bandung City which will be implemented during September 2024 with a total of 8 participants. The target of this health education is ICU nurses. All participants in the activity were given health education about optimizing the use of eye masks, ear plugs and white noise, the knowledge scale was measured before and after the intervention, qualitatively, the health education activities carried out ran smoothly without any obstacles, the health education carried out was able to increase the knowledge of ICU nurses significantly. with p value = <0.001. The results of this health education can increase ICU nurses' knowledge about the use of eye masks, ear plugs and white noise in improving the sleep quality of ICU patients.